2019
DOI: 10.1021/acsami.9b00969
|View full text |Cite
|
Sign up to set email alerts
|

New Family of Two-Dimensional Ternary Photoelectric Materials

Abstract: Screening unique two-dimensional (2D) materials with high mobility and applicable band gaps is motivated by not only the interest in basic science but also the practical applications for photoelectric materials. In this work, we have systematically studied a new family of 2D ternary quintuple layers (QLs), named ABC (A = Na, K, and Rb; B = Cu, Ag, and Au; C = S, Se, and Te).Our results indicate that the QLs of KCuTe, KAgS, KAgSe, KAuTe, RbCuTe, RbAgSe, and RbAgTe host direct band gaps. Moreover, KCuTe, RbCuTe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
(72 reference statements)
2
35
0
Order By: Relevance
“…Also, the special heat transport behaviors may occur in other 2D isostructural materials with ultraweak interlayer interaction, such as layered AAgX (A = Na, K, and Rb; X = S, Se, and Te), which have been recently predicted to possess high carrier mobility and good optical properties. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…Also, the special heat transport behaviors may occur in other 2D isostructural materials with ultraweak interlayer interaction, such as layered AAgX (A = Na, K, and Rb; X = S, Se, and Te), which have been recently predicted to possess high carrier mobility and good optical properties. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, two‐dimensional materials have attracted extensive attention due to their excellent electronic and thermal properties, and they have been widely applied in nanoelectronics, photoelectric devices, and other fields. [ 1 ] In the past two decades, due to the decreasing size of electronic devices, high heat dissipation efficiency, high thermal stability, high conductivity, and high carrier mobility have become important factors determining the performance of electronic devices. [ 2,3 ] Graphene is a famous two‐dimensional carbon material and has received great attention since 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new class of 2D layered semiconductors known as XYZ (X = Rb, K; Y = Au, Ag, Cu; Z = Te, Se, S) have been reported, which have high carrier mobility, moderate band gap, favorable stability, and superior optoelectronic properties. 19–21 Bulk KAgX (X = S, Se, Te) materials were found to possess low and anisotropic lattice thermal conductivity. 22 Very recently, Zhang et al 23 revealed that few-layer KAgSe nanosheets featured intrinsically low lattice thermal conductivity and a considerable power factor due to the strong interlayer vibrations and the complete band-extrema alignment, with an optimal ZT value of 2.08.…”
Section: Introductionmentioning
confidence: 99%